ГЕОМОРФОЛОГИЧЕСКИЕ ЭФФЕКТЫ ЗЕМЛЕТРЯСЕНИЙ 27 СЕНТЯБРЯ И 1 ОКТЯБРЯ 2003 Г. В ГОРНОМ АЛТАЕ - Агатова А.Р.; Новиков И.С.; Высоцкий Е.М.; Гибшер А.С. (My University, 2004)
The relief deformations in the south-eastern part of Gorny Altai caused by strong earthquakes on September 27 -October 1, 2003, were described and some criteria of seismic intensity evaluation for this high mountain region were suggested. The comparison of recent seismogenic deformations with the ancient rock failures and landslides manifests the seismic origin of the latter. Their dimension proves the intensity of ancient earthquakes to be 11-12 according to MSK-64 scale. Concentration of both ancient and recent earthquake-induced deformations in the south-eastern part of Altai indicates that this area is active seismic region at least since Late Pleistocene.
Keywords: Pleistocene; 551.432(235.222); Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен